An Improved Test for Statistical Arbitrage - JARROW, Robert (Institutional Knowledge at Singapore Management University, 2012)
We improve upon the power of the statistical arbitrage test in Hogan, Jarrow, Teo, and Warachka (2004). Our methodology also allows for the evaluation of return anomalies under weaker assumptions. We then compare strategies based on their convergence rates to arbitrage and identify strategies whose probability of a loss declines to zero most rapidly. These strategies are preferred by investors with finite horizons or limited capital. After controlling for market frictions and examining convergence rates to arbitrage, we find that momentum and value strategies offer the most desirable trading opportunities.